Fluence smoothing evaluation for whole‐breast automatically generated treatment plans - Zaratim, Giulianne Rivelli R.; Oliveira e Silva, Luis Felipe; dos Reis, Ricardo G.; Mendes, Cristiano Jacques M. R.; Gomes, Marília Miranda F. (Journal of applied clinical medical physics, 2025)
Purpose This study aimed to identify the fluence smoothing threshold that preserves the dosimetric quality of planning for breast cancer intensity‐modulated radiation therapy (IMRT). Material and methods We conducted automated treatment planning for 60 breast cancer patients using the Eclipse Scripting Application Programming Interface. The plans included four‐field IMRT, emphasizing smoothing weight combinations while maintaining a 4:3 aspect ratio between the X and Y directions. Four weight sets (40 × 30, 100 × 75, 150 × 115.2, and 200 × 150) were tested, resulting in four plans per patient. A total dose of 40.05 Gy over 15 fractions was prescribed. Optimization weigths were dynamically adjusted based on dosimetric evaluations, with the maximum coverage priority set at 200. Statistical analyses were used to assess the dosimetric data. Results The median planning target volume (PTV) coverage varied across smoothing levels, with default smoothing (40 × 30) providing superior median PTV coverage. Lung constraints showed significant differences mainly at higher smoothing levels. Heart constraints exhibited less variation between smoothing levels, with significant differences primarily in the maximum and mean doses for right‐sided patients and between default and higher smoothing levels for left‐sided patients. No significant differences were observed in contralateral breast constraints among all smoothing levels, except at the maximum level for right‐sided patients. Monitor units decreased with increasing smoothing weight, showing significant differences between default and other settings. For right‐sided patients, the median number of monitor units varied from 1346 (40 × 30) to 754 (200 × 150), and for left‐sided patients, from 1333 (40 × 30) to 804 (200 × 150). Chi‐square tests revealed differences in dose constraint adherence between default and maximum smoothing levels, particularly in target coverage. Conclusion Our findings suggest that using a ratio of smoothing weights to target priorities between 1:1.5 and 1:1.6 leads to a favorable balance between complexity and dosimetric plan quality, with no significant impacts on dose constraint adherence.